Effects of maturity on chemical composition and antioxidant activity of sacha inchi (Plukenetia volubilis L.) cultivated in Thailand - Riantong Singanusong; Sudarat Jiamyangyuen (Walailak Journal of Science and Technology, 2018)
Sacha inchi is cultivated commercially in Thailand for its edible kernels and oil.  The highest quality sacha inchi is normally associated with the highest oil content. This study investigated the effects of kernel maturity on chemical composition and antioxidant activity of sacha inchi cultivated in Phitsanulok and Chiang Rai provinces, Thailand. Samples of three maturity stages: green, greenish brown, and brown/dry, were collected on two different harvests. On each harvest day, all three stages were collected from both provinces. There were 12 samples plus two controls. The results show that as the sample maturity increased, moisture content decreased, while oil content increased. The oil content ranged between 38.15-48.81%, protein content 16.23-18.98%, fiber content 14.50-22.24%, ash content 2.70-3.06%, and carbohydrate content 7.70-19.47%. The TPC was 103-385 mg/100 g and antioxidant activity were 9.36-13.72% for DPPH and 5,803.99-10,700 mg Trolox equivalent for FRAP. Average SFA, MUFA and PUFA contents were 3.35, 4.63 and 30.91 g/100 g, respectively. The most common FA was omega 6 PUFA, followed by omega 3 and omega 9. The omega 6 to omega 3 ratio was 1.12-1.56. Samples with the highest oil content were brown/dry samples harvested from Chiang Rai (47.26% oil) and Phitsanulok (46.37% oil), and these were selected to test for amino acids and vitamin E. Nineteen amino acids were detected, with lysine, tyrosine, leucine and glutamic acid predominant. Vitamin E content was 1.02-1.42 mg/100 g.  For the highest quality and greatest health benefits, sacha inchi should be harvested when the shuck is brown and dry.